Marketing Mix of Rubber Factory Waste PT. Darma Kalimantan Jaya DesaHaruyan Seberang Kabupaten Hulu Sungai Tengah - Latte, Jumai; Erpani, Muhammad (Magister Administrasi Bisnis ULM, 2024)
Abstract: This research aims to provide an overview of the marketing mix from the utilization of waste from PT rubber factory production. PT Darma Kalimantan Jaya, so that it can become a product that has economic value among the community and what is the marketing process. This type of research is field research with a qualitative descriptive approach. The purposeful sampling data analysis technique and data credibility test used is triangulation. The results of the research carried out can be concluded that by indirectly applying the concept of the 7p marketing mix as in Kotler and Fox's theory in (Lupiyoadi, 2013: 148) in the waste soil product business managed by PT. Darma Kalimantan Jaya has been able to attract interest from buyers to become customers and has been able to become a strength and advantage in facing competition with other waste land entrepreneurs, because PT. Darma Kalimantan Jaya really maintains the quality of its products, and prioritizes always providing the best service to each customer in order to create comfort and satisfaction for all customers who come to buy products from this waste land Keywords: Marketing Mix Strategy, Marketing Concept